Hydatid Cyst of the Rib: A New Case and Review of the Literature - A. Chafik; A. Benjelloun; A. El Khadir; R. El Barni; A. Achour; M. A. Ait Benasser (Case Reports in Medicine)
The hydatid cyst is not rare in our country, but bone lesions are less common. The disease often takes the appearance of abscess or malignant lesion. We report a case of a 35-year-old man with a hydatid cyst of the rib complicated with cutaneous fistula. The surgery allowed both diagnosis and treatment. Albendazole was then administered to prevent relapse.